A climatology of 7Be in surface air in European Union. (March 2015) - Hernández-Ceballos, M.A.; Cinelli, G.; Marín Ferrer, M.; Tollefsen, T.; De Felice, L.; Nweke, E.; Tognoli, P.V.; Vanzo, S.; De Cort, M.
Abstract: This study presents a European-wide analysis of the spatial and temporal distribution of the cosmogenic isotope 7 Be in surface air. This is the first time that a long term database of 34 sampling sites that regularly provide data to the Radioactivity Environmental Monitoring (REM) network, managed by the Joint Research Centre (JRC) in Ispra, is used. While temporal coverage varies between stations, some of them have delivered data more or less continuously from 1984 to 2011. The station locations were considerably heterogeneous, both in terms of latitude and altitude, a range which should ensure a high degree of representativeness of the results. The mean values of 7 Be activity concentration presented a spatial distribution value ranging from 2.0 to 5.4 mBq/m 3 over the European Union. The results of the ANOVA analysis of all 7 Be data available indicated that its temporal and spatial distributions were mainly explained by the location and characteristic of the sampling sites rather than its temporal distribution (yearly, seasonal and monthly). Higher 7 Be concentrations were registered at the middle, compared to high-latitude, regions. However, there was no correlation with altitude, since all stations are sited within the atmospheric boundary layer. In addition, the total and yearly analyses of the data indicated a dynamic range of 7 Be activity for each solar cycle and phase (maximum or minimum), different impact on stations having been observed according to their location. Finally, the results indicated a significant seasonal and monthly variation for 7 Be activity concentration across the European Union, with maximum concentrations occurring in the summer and minimum in the winter, although with differences in the values reached. The knowledge of the horizontal and vertical distribution of this natural radionuclide in the atmosphere is a key parameter for modelling studies of atmospheric processes, which are important phenomena to be taken into account in the case of a nuclear accident. Highlights: First European-wide analysis of the 7 Be in surface air. Temporal and spatial variability of 7 Be during 1984–2011 period. Impact of the 11-y solar modulation on the 7 Be concentrations in Europe.